الضيافة والكرم في ضوء تفسير الشعراوي : دراسة تحليلية - Ahmad Salahuddin bin 'Azizan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research deals with the issue of hospitality and generosity in the light of Tafsir al-‎Sha'rawi and analyses the views of Sheikh Al-Sha'rawi on this particular issue. The ‎importance of this issue is highlighted by the attention given by a vast number of ‎scholars on the finesse of the hospitality and generosity in numerous fields such as in ‎business transactions, companies, hotels and government and educational institution ‎alike, which is usually promoted to get profits without taking into consideration Shariah ‎regulations throughout the process. Hence, this research seeks to tackle this issue by ‎looking into the Quranic verses related to this matter, of al-Sha'rawi's interpretation ‎through his magnum opus, the Tafsir al-Sha'rawi. Two main approaches had been ‎utilised by the researcher in conducting this study: inductive and analytical analysis. For ‎the first method, the researcher brought about all of the Quranic verses related to the ‎subject, collected them and accordingly categorised them into some classifications. The ‎latter method was then used to analyse the collected Quranic verses interpreted by al-‎Sha'rawi, as well as some analysis on the Prophet's traditions related to the subject ‎matter. At the end of the study, the research concludes that most of the interpretation of ‎Quranic verses by al-Sha'rawi related to the subject matter are in line with the concept ‎of hospitality and generosity.